SISTEM INFORMASI AKADEMIK BERBASIS FRAMEWORK BOOTSTRAP UNTUK PENGELOLAAN DATA AKADEMIK DAN ADMINISTRASI - Ridwan, Muhammad; Yusuf, Arief Rahman (SULIWA: Jurnal Multidisiplin Teknik, Sains, Pendidikan dan Teknologi, 2025)
The rapid development of information technology has not been fully utilized in schools, especially in the management of academic data which is still done manually. This causes low work efficiency and difficulty in accessing information. An efficient and integrated academic information system is needed. This research aims to design and implement a web-based academic information system using the Bootstrap framework for academic data management. This system includes features for managing student, teacher, schedule, grade, and attendance data with a responsive display that can be accessed from various devices. The development method used is the waterfall model, through needs analysis, design, implementation, and testing. The test results show that this system is effective in managing academic data and facilitating access to information for users. In conclusion, this system offers a practical and efficient solution. Suggestions for further development include integration with online learning systems and improving user data security.